ТАРИЙХЫЙ ФОЛЬКЛОР ҲӘМ ТАРИЙХЫЙ ҲАҚЫЙҚАТЛЫҚ (Үстирттеги тарийхый естеликлерге байланыслы аңыз-рәўиятлар ҳаққында) - Қанаатов, Е.Е. (ILIM hám JÁMIYET, 2024)
The article talks about the historical reality in legends and parables about the historical monuments of Ustyurt. The author conducts a historical and linguistic analysis of why historical places called Puljay, Tengeshashkan and Dzhezkempir received such a name. Readers are also offered interesting information about the sacred place in the southeastern part of Ustyurt - the mausoleum and cemetery of King Ibrahim Adham.